2005
DOI: 10.1128/aem.71.11.6673-6679.2005
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Associated with Spores of the Arbuscular Mycorrhizal Fungi Glomus geosporum and Glomus constrictum

Abstract: Spores of the arbuscular mycorrhizal fungi (AMF) Glomus geosporum and Glomus constrictum were harvested from single-spore-derived pot cultures with either Plantago lanceolata or Hieracium pilosella as host plants. PCR-denaturing gradient gel electrophoresis analysis revealed that the bacterial communities associated with the spores depended more on AMF than host plant identity. The composition of the bacterial populations linked to the spores could be predominantly influenced by a specific spore wall compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 33 publications
3
101
0
3
Order By: Relevance
“…Therefore, symbiotic fungus behaves in an identical manner to the arbuscular mycorrhizal fungi (AMF) in stimulating the PGPR activity in the rhizosphere of crop, as reported by Werner (2001) and Kohler et al (2007). Roesti et al (2005) reported the stimulation of exophytic PGPR in wheat rhizosphere following inoculation with arbuscular mycorrhizal fungi. The arbuscular mycorrhizal fungi (AMF) was found to play a dominant role in comparison to (wheat) host crop in promoting exophytic colonization.…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, symbiotic fungus behaves in an identical manner to the arbuscular mycorrhizal fungi (AMF) in stimulating the PGPR activity in the rhizosphere of crop, as reported by Werner (2001) and Kohler et al (2007). Roesti et al (2005) reported the stimulation of exophytic PGPR in wheat rhizosphere following inoculation with arbuscular mycorrhizal fungi. The arbuscular mycorrhizal fungi (AMF) was found to play a dominant role in comparison to (wheat) host crop in promoting exophytic colonization.…”
Section: Discussionmentioning
confidence: 69%
“…decipiens were able to colonize the interior of the spores demonstrating AM colonization does not occur on AM surfaces only through biofilm formation (Levy et al, 2003). Bacterial saprophytic activity was also suggested by scanning electron microscopy observations of G. geosporum spores (Roesti et al, 2005). The spore's outer layer was shown to be eroded and to be covered by mucilaginous products suggesting that AM fungi can be directly consumed by bacteria.…”
Section: Mechanisms Of Interactions Between Amb and Am Extraradical Nmentioning
confidence: 85%
“…From mycorrhizosphere and AM structures, various rhizobacteria (named AM-associated rhizobacteria, AMB) (especially Paenibacilli, Bacilli and Pseudomonas spp.) were identified by classical culturedependant methods (Andrade et al, 1997;Budi et al, 1999;Mansfeld-Giese et al, 2002;Lioussanne, 2007;Bharadwaj et al, 2008b), phospholipid fatty acid analysis (PLFA) (Rillig et al, 2005) and PCR-DGGE (Polymerase chain reaction-Denaturing gradient gel electrophoresis; Xavier and Germida, 2003;Roesti et al, 2005;Lioussanne, 2007) reinforcing the hypothesis that AM structures constitute important nutrient-rich niches for soilborne microorganisms. Candidatus Glomeribacter gigasporarum (proposed as a new taxon of Burkholderiaceae) was even described as a Gram-noncultivable (thus obligatory) bacterial endosymbiot of spore vacuoles, mycelium and intraradical hyphae of Gigaspora margarita colonizing clover plants (Bianciotto et al, 1996b;Bianciotto and Bonfante, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…UP2338) roots grown in marginal soils of Bhawanipur, District Budaun, Uttar Pradesh, India (13,14). These two strains displayed a high potential for use as biofertilizers of wheat in India (7,14). In long-term field experiments conducted in the IndoGangetic plains, they increased the yield and grain quality of wheat and other crop plants substantially, particularly in combination with arbuscular mycorrhizal fungi (12).…”
mentioning
confidence: 99%
“…UP2338) roots grown in marginal soils of Bhawanipur, District Budaun, Uttar Pradesh, India (13,14). These two strains displayed a high potential for use as biofertilizers of wheat in India (7,14).…”
mentioning
confidence: 99%